2013
DOI: 10.1007/s00429-013-0620-9
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-region hemispheric specialization differentiates human from nonhuman primate brain function

Abstract: The human behavioral repertoire greatly exceeds that of nonhuman primates. Anatomical specializations of the human brain include an enlarged neocortex and prefrontal cortex (Semendeferi et al. in Am J Phys Anthropol 114:224–241, 2001), but regional enlargements alone cannot account for these vast functional differences. Hemispheric specialization has long believed to be a major contributing factor to such distinctive human characteristics as motor dominance, attentional control and language. Yet structural cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
2
31
1
Order By: Relevance
“…This parallels findings from fMRI, whose network structures also appear largely immune to changes in consciousness (Vincent et al 2007;Horovitz et al 2008;Boly et al 2009;Wey et al 2014). This is difficult to understand in light of the profound influences that sleep and anesthesia have on nearly all other aspects of brain physiology, including the raw ECoG signals that serve as the basis of the covariation analysis.…”
Section: Broadband Characteristics Of Network Activitysupporting
confidence: 63%
See 1 more Smart Citation
“…This parallels findings from fMRI, whose network structures also appear largely immune to changes in consciousness (Vincent et al 2007;Horovitz et al 2008;Boly et al 2009;Wey et al 2014). This is difficult to understand in light of the profound influences that sleep and anesthesia have on nearly all other aspects of brain physiology, including the raw ECoG signals that serve as the basis of the covariation analysis.…”
Section: Broadband Characteristics Of Network Activitysupporting
confidence: 63%
“…To address these shortcomings, we investigated large-scale covariation of electrophysiological signals with electrocorticography (ECoG) arrays implanted over an extensive portion of the left hemispheric surface of macaque monkeys, whose spontaneous brain activity has been extensively studied with fMRI (Vincent et al 2007;Moeller et al 2009;Hutchison et al 2011;Hutchison and Everling 2012;Wey et al 2014) and was found to have covariational structures that resemble those found in human (Hutchison and Everling 2012;Wey et al 2014). The ECoG data, which covered a broad spectral range, were analyzed with a novel data-driven clustering approach, which has previously been used for analyzing resting-state fMRI signals .…”
Section: Introductionmentioning
confidence: 99%
“…Lateralization develops by coopting brain areas which have an evolutionary subordinate function into a network of hemispheric sites tasked with the analysis of complex information and the performance of complex tasks. In this regard, Wey et al (342) compared network lateralization between three non-human primate species and humans. They point out that functional studies show more hemispheric asymmetry in humans than generally identifiable in neuroanatomical structural analysis.…”
Section: A Note On Lateralizationmentioning
confidence: 99%
“…The baboon brain also has a larger degree of gyrification (folding) than other Old World monkeys and contains all the primary cortical structures found in humans (Rogers et al, 2010). Accordingly, the baboon model has been used in numerous structural and functional neuroimaging experiments (e.g., Kochunov et al, 2010aKochunov et al, , 2010bKroenke et al, 2005Kroenke et al, , 2007Liu et al, 2008;Miller et al, 2013;Phillips and Kochunov, 2011;Phillips et al, 2012;Rogers et al, 2007;Salinas et al, 2011;Szabo et al, 2007Szabo et al, , 2011aSzabo et al, , 2011bWey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%